Numerical-analytical method in the case of degenerate matrices in boundary conditions - Ronto , N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A modification of the numerical analytic method of successive approximations is proposed for investigating the existence and constructing solutions of systems of nonlinear ordinary differential equations with two-point linear boundary conditions. The method is tailored to the case where the matrices contained in boundary conditions are singular, but their linear combination is nonsingular.